PENYELESAIAN SENGKETA TANAH SAWAH GILIR GANTI PADA MASYARAKAT HUKUM ADAT KERINCI - David Herlambang; Zulfikar Jayakusuma; Hengki Firmanda S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Dispute resolution is expected not only to win or lose but to try to reach an agreement between the parties in dispute with consensus and win-win solution This article describes how the settlement of disputes that occur in the Kerinci customary law community in the Regency Kerinci, Jambi Province. Writing this article is taken from the results of research with this type of research conducted with the type of research to be used is sociological juridical (empirical legal research) that is empirical studies to find theories about the process of occurrence and about the process of working of law in society. Efforts to resolve disputes through mediation certainly do not always succeed in achieving peace between the disputing parties. The problem that often occurs in the Kerinci customary law community is the problem of managing the shifting paddy land instead of the Kerinci customary law community which is a typical inheritance system belonging to the Kerinci indigenous people. Settlement of disputes in Kerinci customary law has 4 levels, namely kitchen institutions, institutions, traditional institutions and natural institutions. The dispute resolution process began in stages starting from Tengganai to Depati. The purpose of writing this thesis is first To find out the management system of the shifting paddy field system in the Kerinci customary law community, second To find out the settlement of the dispute from the rotating paddy field using Kerinci customary law in the Kerinci customary law community and third As a brainstorm of the writer's thoughts on the alma mater in adding khasanah civil law and customary law relating to the resolution of the rotating paddy field dispute in the Kerinci customary law community.Keywords: Indigenous Institutions, Legal, Dispute Resolution